2006
DOI: 10.1097/00129234-200607000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Children With Special Healthcare Needs in the Managed Care Environment

Abstract: Dramatic medical and technological advances over the past 15 years have resulted in the survival into adulthood of children with chronic health conditions. As this population subset has increased, the demand of caring for these children in the managed care arena has become challenging from a clinical, fiscal, and member satisfaction perspective. A disease management program was designed for children, ages birth through age 18, identified as having special needs at the time of birth or at any point throughout c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Care in this medical home was also primary care–based with professionals in nutrition, gastroenterology, neurology, and allergy/immunology available once monthly. Similar hospital cost avoidance has been shown using primary care– or nurse practitioner–based models for CSHCN . To our knowledge, ours is the first study to suggest a decrease in hospital stay for patients with multiple aerodigestive comorbidities treated by a physician-led, multidisciplinary, specialty care model that emphasizes partnership with community-based primary care pediatricians.…”
Section: Discussionsupporting
confidence: 72%
“…Care in this medical home was also primary care–based with professionals in nutrition, gastroenterology, neurology, and allergy/immunology available once monthly. Similar hospital cost avoidance has been shown using primary care– or nurse practitioner–based models for CSHCN . To our knowledge, ours is the first study to suggest a decrease in hospital stay for patients with multiple aerodigestive comorbidities treated by a physician-led, multidisciplinary, specialty care model that emphasizes partnership with community-based primary care pediatricians.…”
Section: Discussionsupporting
confidence: 72%
“…23 This standalone care-manager model has the advantage of the delegation of nonclinical, often time-intensive duties to staff who ideally have increased community insight, and connections are often less costly to the health care system than advanced medical providers. 20 A few evaluations of insurance caremanager programs have revealed cost savings and improved diseasespecific outcomes for children with chronic conditions 24,25 ; however, there remains little evaluative literature on this model overall or specifically for CMC.…”
Section: General Principles For Models Of Care For Cmcmentioning
confidence: 99%
“…Similar to our findings, despite the largely positive findings reported, the authors found generally weak study designs, inconsistent outcome measures, and a lack of comparison groups in most studies. Although the medical home model is meant to be a primary care community-based model, there was some overlap in their article and ours owing to liberal inclusion criteria in both reviews; 6 studies 26,39,42,49,50,57 among the 30 were included in our review. Some studies in the review by Homer et al 61 were hospital based and included only parts of the medical home model, while some studies herein included a substantial community-based component.…”
Section: Commentmentioning
confidence: 99%